ANS: 16
EQ 1=> X+X=20; 2X=20; X=10;
EQ 2=> X+Y=14; 10+Y=14; Y=4;
EQ 3=> Y+Z+Z=8; 4+2Z=8; 2Z=4; Z=2;
EQ 4=> X+Z+Y= 10+2+4= 16

ANS: 15
EQ 3=> X=8-X; 2X=8; X=4;
EQ 2=> 2=X-Y; 2=4-Y; 2=Y;
EQ 1=> Z+Z=Y; 2Z=2; Z=1;
EQ 4=> X+W=12; 4+W=12; W=8;
EQ 5=> Z+X+Y+W=1+4+2+8= 15;

ANS: 12
EQ 1=> X+X+X=39; 3X=39; X=13
EQ 2=> X+Y=16; 13+Y=16; Y=16-13; Y=3;
EQ 3=> Z=2Y; Z=2*3; Z= 6;
EQ 4=> Z+Z=12

ANS: 8
EQ 3=> X=Y;
EQ 2=> X+X+Y=21; (Y=X In EQ 3) X+X+X=21; X=7;
EQ 4=> X-5=Z; 7-5=Z; 2=Z;
EQ 1=> W+Z+W=18; 2W+2=18; 2W=16; W=8;

ANS:4
EQ 2=> 12-X=X; 12= 2X; 6=X;
EQ 3=> X+Y=31; 6+Y=31; Y=25;
EQ 1=> Y+Z=40; 25+Z=40; Z=15;
EQ 4=> Y-Z+X=? 25-15+6= 25-21= 4

ANS: 16
EQ 1=> X+Y=13; X=13-Y
EQ 2=> Y-Z=5;
EQ 3=> X-Z=2
Subtract EQ 3 from EQ 2 Then We Get Y – X=3
NOW subtract Y-X=3 From X+Y=13 Then We Get X+X=10; 2X=10; X=5;
Put X=5 in EQ 1 => X+Y=13; Y=8;
EQ 3 => X-Z=2; -Z=2-5; Z=3;
EQ 4=> X+Y+Z= 5+8+3= 16

ANS: 1
EQ 2=> 3*X=33; X=33/3; X=11;
EQ 3=> X-Y=7; 11-Y=7; -Y=7-11; Y=4;
EQ 4=> Z-3=Y; Z-3=4; Z=4+3; Z=7;
EQ 1=> Z+Z-W=X=> 2Z-W=13; 2(7)-W=13; 14-W=13; -W=13-14; W=1;

ANS: 29
EQ 4=> Y=X EQ 1=> 39=2X+Y (In Equation 4 => Y=X) Then 39= 2X+X => 39=3X; X=13;
EQ 2=> X-Z=10; 13-Z=10; -Z=10-13; Z=3;
EQ 3=> W=2*Z; W=2*3; W=6;
EQ 5=> X+w+Y-Z=? => 13+6+13-3= 32-3= 29

puzzle

puzzle

puzzle

puzzle

puzzle

puzzle